The predictive significance of CD20 expression in B-cell lymphomas - Horvat Mateja; Lavrenčak Jaka; Prevodnik Veronika; Novakovič Barbara (BMC, 2011)
Abstract Background In our recent study, we determined the cut-off value of CD20 expression at the level of 25 000 molecules of equivalent soluble fluorochrome (MESF) to be the predictor of response to rituximab containing treatment in patients with B-cell lymphomas. In 17.5% of patients, who had the level of CD20 expression below the cut-off value, the response to rituximab containing treatment was significantly worse than in the rest of the patients with the level of CD20 expression above the cut-off value. The proportion of patients with low CD20 expression who might not benefit from rituximab containing treatment was not necessarily representative. Therefore the aim of this study was to quantify the CD20 expression in a larger series of patients with B-cell lymphomas which might allow us to determine more reliably the proportion of patients with the CD20 expression below the cut-off. Methods Cytological samples of 64 diffuse large B-cell lymphomas (DLBCL), 56 follicular lymphomas (FL), 31 chronic lymphocytic leukemias (CLL), 34 mantle cell lymphomas (MCL), 18 marginal zone lymphomas (MZL) and 15 B-cell lymphomas unclassified were analyzed for CD20 expression by quantitative four-color flow cytometric measurements using FACSCalibur flow cytometer (BD Biosciences). Results The range of CD20 expression in different B-cell lymphomas was very broad, varying from 2 737 to 115 623 MESF in CLL and 3 549 to 679 577 MESF in DLBCL. However, when we compared the CD20 expression in the groups of patients with DLBCL, FL, MCL, MZL, CLL and B-cell lymphomas unclassified, it was found to be significantly lower (p = 0.002) only in CLL but did not significantly differ in other lymphoma types (p = NS). Fifty-three out of 218 (24.3%) patients with B-cell lymphomas had the CD20 expression below the cut-off value. Conclusions The CD20 expression in CLL is significantly lower than in most histological types of mature B-cell lymphomas in which it appears to be comparable. Approximately 25% of B-cell lymphoma patients have the CD20 expression below the cut-off value showing that the low CD20 expression might be more common than presumed from our previous study.